Cm
\(\sqrt{6\sqrt{6+\sqrt{6}}}\)<9
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(\dfrac{2}{\sqrt{6}-1}+\dfrac{3}{\sqrt{6}-2}-\dfrac{3}{3-\sqrt{6}}\right)\cdot\dfrac{5}{9\sqrt{6}+4}\)
\(=\left(\dfrac{2+2\sqrt{6}}{5}+\dfrac{6+3\sqrt{6}}{2}-3-\sqrt{6}\right)\cdot\dfrac{5}{9\sqrt{6}+4}\)
\(=\dfrac{4+4\sqrt{6}+30+15\sqrt{6}-30-10\sqrt{6}}{10}\cdot\dfrac{5}{9\sqrt{6}+4}\)
\(=\dfrac{1}{2}\)
Cho \(A=\sqrt{6+\sqrt{6...+\sqrt{6}}+\sqrt[3]{6+\sqrt[3]{6...+\sqrt[3]{6}}}}\) Chứng minh rằng 4<A<5
Cho \(A=\sqrt{6+\sqrt{6...+\sqrt{6}}+\sqrt[3]{6+\sqrt[3]{6...+\sqrt[3]{6}}}}\) Chứng minh rằng 4<A<5
\(\sqrt{6\sqrt{6+\sqrt{6}}}< \sqrt{6\sqrt{6+\sqrt{9}}}\)
\(=\sqrt{6\sqrt{6+3}}=\sqrt{6\sqrt{9}}\)
\(=\sqrt{6.3}< \sqrt{81}=9\)
Vậy \(\sqrt{6\sqrt{6+\sqrt{6}}}< 9\)